Impact of Birth Order on Personality Traits of College Students - Dr. Umakant Subhash Gaikwad (International Journal of Indian Psychȯlogy, 2022)
An Objectives of the study: To search the impact of birth order on personality traits of college students. Hypothesis: There will be no significant impact found of birth order on personality traits among college students. Sample: The total sample comprised of 160 college students was selected. Birth order is used as type-E variable for the present research. Based on the Birth order, two groups of students were formed, namely students with First Born (N= 80) and students with Last Born college students (N= 80) belonging to Chhatrapati Sambhajinagar District Maharashtra state. Non-Probability Purposive sampling was used for the present study. Research Tools 1. Dimensional Personality Inventory (DPI):- developed and standardized by Mahesh Bhargava in 2002, is composed of 60 items. Statistical Analysis: “t” value Statistics is used for the present study. Conclusions 1. First born college students had significantly high Activity than the last-born college students (Passivity). 2. First born college students had significantly high Enthusiastic than the last-born college students (non-enthusiastic). 3. First born college students had significantly high Assertive than the last-born college students (Submissive). 4. First born college students had significantly high Trusting than the last-born college students (Suspicious). 5. First born college students had significantly high Non-Depressive than the last born college students (Depressive). 6. First born college students had significantly high Emotional Stability than the last-born college students (Emotional instability).